Next Generation Computer Animation Techniques: Third International Workshop, AniNex 2017, Bournemouth, UK, June 22-23, 2017, Revised Selected Papers - Chang, Jian; Zhang, Jian Jun; Magnenat Thalmann, Nadia; Hu, Shi-Min; Tong, Ruofeng; Wang, Wencheng (Lecture Notes in Computer Science, 2017)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International Workshop on Next Generation Computer Animation Techniques, AniNex 2017, held  in Bournemouth, UK, in June 2017. The workshop was held in conjunction with the 11th International Conference on E-Learning and Games, Edutainment 2017. The 17 full papers presented in this volume were carefully reviewed and selected from 27 submissions. The papers are structured  according to the four main themes: simulation and rendering for computer animation; character modeling and dynamics; user centered design and modeling; computer animation systems and virtual reality based applications.